1998
DOI: 10.1002/(sici)1521-3757(19980703)110:13/14<1940::aid-ange1940>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Selbstorganisation eines supramolekularen tetraedrischen M4L6-Clusters

Abstract: Nicht zu groß und nicht zu klein sollte der Gast im Hohlraum sein: Der homochirale tetraedrische Cluster [Ga4L6]12− weist eine hohe Selektivität für den Einschluß von Et4N+ gegenüber Pr4N+ auf, das seinerseits eingeschlossenes Me4N+ verdrängt (L=zweifach zweizähniger Ligand); dieser sukzessive Austausch von R4N+‐Ionen verläuft 1H‐NMR‐spektroskopischen Untersuchungen zufolge schnell und quantitativ (siehe unten). Der Einschluß von Et4N+ wurde auch im Festkörper nachgewiesen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0
15

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(97 citation statements)
references
References 21 publications
4
78
0
15
Order By: Relevance
“…dividing the surface of a sphere [1d, e] (for example, two hemispherical halves, [5] two non-hemispherical sections, [6] four quarters, [7] ) or of a polyhedron [1b, c] (for example, tetrahedron, [8] icosahedron, [9] snub cube, [10] triangular prism [11] ) into complementary elements. Herein we present a new approach for preparing unimolecular capsules from a molecular strand folded into a helix, the diameter of which is large at the center and reduced at both ends-similar to the shape of the skin of an apple peeled in a helical fashion.…”
mentioning
confidence: 99%
“…dividing the surface of a sphere [1d, e] (for example, two hemispherical halves, [5] two non-hemispherical sections, [6] four quarters, [7] ) or of a polyhedron [1b, c] (for example, tetrahedron, [8] icosahedron, [9] snub cube, [10] triangular prism [11] ) into complementary elements. Herein we present a new approach for preparing unimolecular capsules from a molecular strand folded into a helix, the diameter of which is large at the center and reduced at both ends-similar to the shape of the skin of an apple peeled in a helical fashion.…”
mentioning
confidence: 99%
“…Triethylphosphine was purchased from Aldrich and used as received. Na 12 [Ga 4 L 6 ] [15] and [Me 2 C(OH)PEt 3 ][Br] [19] were synthesized by using published procedures.…”
Section: Methodsmentioning
confidence: 99%
“…That the 115-atom 3-shell core of 1 (i.e., minus the 30 capping atoms) was actually proposed by Farges et al [14] as a possible full-shell structural model for noble-gas clusters produced in free-jet expansion into a vacuum is somewhat astonishing (i.e., mass spectra of charged noble-gas clusters provide no subshell magic-number evidence for the 115-atom cluster being particularly abundant because of special stability [14,15] ). Their model represents a geometrical modification of the classic Mackay hard-sphere multilayer icosahedral (MIC) models based upon a 13-atom centered icosahedron being considered as 20 identical (slightly distorted) fcc tetrahedra that share a common vertex and are connected to one another through adjacent shared faces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the synthesis of this molecule does not rely on a guest molecule (according to NMR spectral data); however, the single crystal X-ray structure of the cluster reveals four guest molecules filling the large void volume of the cluster. Raymond and coworkers [52,118] have also shown that single crystal growth necessitates the use of a guest in two of their systems in which the guest molecule is not vital for cluster formation in solution. These findings have paved the way for exploring a variety of guest-assisted self-assembly reactions to form tetrahedral clusters.…”
Section: Tetrahedra and Adamantanoidsmentioning
confidence: 99%